Avicenna in medieval Hebrew translation - Elgrably-Berzin, Gabriella. (Leiden ; Boston)
x, [1], 223 s.
Keywords: "In this volume, Gabriella Elgrably-Berzin offers an analysis of the fourteenth-century Hebrew translation of a major eleventh-century philosophical text: Avicenna’s Kitāb al-Najāt (The Book of Salvation), focusing on the psychology treatise on physics. The translator of this work was Ṭodros Ṭodrosi, the main Hebrew translator of Avicenna’s philosophical writings. This study includes a critical edition of Ṭodrosi’s translation, based on two manuscripts as compared to the Arabic edition (Cairo, 1938), and an appendix featuring the section on metaphysics. By analyzing Ṭodrosi’s language and terminology and making his Hebrew translation available for the first time, Berzin’s study will help enable scholars to trace the borrowings from Todrosi’s translations in Jewish sources, shedding light on the transmission and impact of Avicenna’s philosophy." --